Effect of a See and Treat clinic on skin cancer treatment time. Issue 5 (11th October 2017) - McLaughlin, Scott J. P.; Kenealy, John; Locke, Michelle B.
Abstract : Background: Many plastic surgery departments in Australasia have experienced increasing referrals for management of skin lesions. This has driven a demand for new strategies to decrease patient waiting time and administrative costs. The aim of this study was to determine if a purpose‐built See and Treat skin cancer clinic could provide a faster skin cancer treatment pathway with comparable clinical outcomes and acceptability to patients. Methods: This was a prospective observational study of patients treated through the See and Treat clinic with a retrospective control cohort. The prospective 'See and Treat' cohort included a consecutive series of 106 patients, while the retrospective cohort included a consecutive series of 200 patients. Patient demographics, time from referral to surgery and operative measures were analysed. One hundred patients in the prospective cohort completed an anonymous satisfaction survey regarding their treatment. Results: The average time from referral to surgery was reduced from 121 days in the retrospective cohort to 60 days in the See and Treat cohort ( P  < 0.001). Rates of complete excision of malignant and premalignant lesions were not different between the two groups, being 93% (178/191) and 91% (76/84), respectively ( P  = 0.609). Ninety‐five percent (95/100) of patients were satisfied with their See and Treat experience overall. Conclusion: We show that a considerable reduction in the time between referral and surgery can be achieved through a See and Treat clinic without compromise of the success of surgical treatment. Moreover, such a treatment pathway has been shown to be acceptable, and largely preferable, to patients.